Peran Mediasi Ganda Kredibilitas Merek dan Electronic Word of Mouth (e-WOM) dalam Efektivitas Influencer Marketing terhadap Keputusan Pembelian Konsumen - Reni Yesi S; Budi Rachmawati; Murdan Sianturi (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2025)
This study aims to analyze the effects of influencer marketing, electronic word of mouth (e-WOM), and brand credibility on consumer purchase decisions, as well as to examine the dual mediating roles of brand credibility and e-WOM. A quantitative research approach was employed using a survey method involving 200 active social media users in Indonesia. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results indicate that influencer marketing has a positive and significant effect on consumer purchase decisions, brand credibility, and e-WOM. Brand credibility also shows a significant positive effect on purchase decisions, while e-WOM does not have a significant influence. The mediation analysis reveals that brand credibility significantly mediates the relationship between influencer marketing and consumer purchase decisions, whereas e-WOM does not. These findings highlight that the effectiveness of influencer marketing is primarily driven by its ability to build consumer trust and enhance brand credibility rather than by online buzz or social diffusion. Theoretically, this study reinforces the Source Credibility Theory and Trust Transfer Theory, while practically it provides insights for marketers to prioritize collaborations with authentic influencers whose values align with the brand.